Instigation in the Iraqi theatrical discourse: حسين رضا حسين (Al-Academy, 2016)
The first chapter included the frame approach on research in which we discuss instigation in Iraqi drama as it as an active sign to enrich the structure of the speech so the researcher limits the problem of his research which is to follow the important of instigation in the Iraqi theatrical discourse. this chapter also contains the important of the research and its aim and limits. And reflected the importance of research in approaching the concept of instigation and effectiveness within the paths of the Iraqi, theatrical discourse.The 2nd chapter included the two sections and reviewed in the first section manifestations of incitement in the global theatrical discourse. the 2rd studied instigation in the Arab theatrical discourse. The 3rd chapter included research applications. The researcher adopted the descriptive method as an approach to analyses the research. The 4th chapter included the following result and conclusions; 1.The instigation can be seen clearly and directly in the play" Rehearsal in the hell" and it is codded for the 2nd time in "Orientalist Bedwin". Then the researcher present the results conclusion add bibliography